Non-linear Controller to push PV system produce Maximum Power Point - FEIDJEL Abderrahmane; BENSAFIDDINE Ahmed Nadir; OUBBATI Brahim Khalil (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
This master’s thesis focuses on the realization of a nonlinear control strategy aimed at achieving maximum energy extraction from photovoltaic (PV) modules. The aim of this work is to improve the performance and efficiency of photovoltaic systems by developing a control strategy that dynamically adjusts the point of operation of the photovoltaic module. It begins with an overview of solar energy and photovoltaic systems, providing a foundation for understanding the principles and components of photovoltaic technology. It also delves into the study of DC-DC converters and Maximum Power Point Tracking (MPPT) algorithms, highlighting their importance in extracting the maximum available power from a PV module. Extensive simulations of different MPPT algorithms have been performed to evaluate their effectiveness in maximizing energy production by the photovoltaic system. Finally, this Master thesis focused on the experimental implementation of the nonlinear controller. Realworld experiments are performed to verify the performance and feasibility of the proposed nonlinear control strategy. The experimental results demonstrate the practical application and effectiveness of the developed nonlinear controller algorithm in achieving the maximum energy extraction from the photovoltaic module. Integral Sliding Mode controller, PI regulator, photovoltaic, Maximum Power Point Tracking, Hill-Climbing, DC-DC converter.Integral Sliding Mode controller, PI regulator, photovoltaic, Maximum Power Point Tracking, Hill-Climbing, DC-DC converter.
SPECIALTY: Instrumentation